Retinoblastoma: diagnosis and management—the UK perspective. Issue 11 (4th May 2015) - Jenkinson, Helen
Abstract : In the developed world, retinoblastoma is an uncommon yet highly curable ocular malignancy of childhood affecting 40–50 children in the UK each year. The presenting signs, most commonly leukocoria and squint, should alert the primary care physician or secondary care physician to examine for the red reflex, the absence of which is an indication for urgent ophthalmology assessment. Diagnosis is made by clinical examination and staging may include bone marrow sampling, lumbar puncture and MRI scanning. CT should be avoided to reduce radiation exposure in a population of whom a proportion are at considerable risk of second malignancies. Although enucleation is necessary for many children, over recent years there has been a growing emphasis on conservative management in an attempt to reduce the need for enucleation and avoid the adverse late effects associated with external beam radiotherapy. This review will describe approaches to treatment in the UK and how the stage, laterality and position of the tumour within the eye influence treatment choices.